The FG 2015 Kinship Verification in the Wild Evaluation - Jiwen Lu; Junlin Hu; Liong, Venice Erin; Xiuzhuang Zhou; Bottino, Andrea; Ul Islam, Ihtesham; Figueiredo Vieira, Tiago; Xiaoqian Qin; Xiaoyang Tan; Songcan Chen; Mahpod, Shahar; Keller, Yosi; et al. (2015 11th IEEE International Conference and Workshops on Automatic Face and Gesture Recognition (FG), 2015)
The aim of the Kinship Verification in the Wild Evaluation (held in conjunction with the 2015 IEEE International Conference on Automatic Face and Gesture Recognition, Ljubljana, Slovenia) was to evaluate different kinship verification algorithms. For this task, two datasets were made available and three possible experimental protocols (unsupervised, image-restricted, and image-unrestricted) were designed. Five institutions submitted their results to the evaluation: (i) Politecnico di Torino, Italy; (ii) LIRIS-University of Lyon, France; (iii) Universidad de Las Palmas de Gran Canaria, Spain; (iv) Nanjing University of Aeronautics and Astronautics, China; and (v) Bar Ilan University, Israel. Most of the participants tackled the image-restricted challenge and experimental results demonstrated better kinship verification performance than the baseline methods provided by the organizers.